The shaping of an effective leader : eight formative principles of leadership - Beebe, Gayle D. (Downers Grove, Ill. : IVP Books, 2011)
Gayle Beebe, who has spent over a decade as a college president, had the opportunity to study with Peter Drucker, the father of modern management and the author of The Effective Executive. Drawing on Drucker's influence, as well as, his own years of experiences as a pastor, administrator and president, Beebe has developed a pyramid of leadership principles. The combination of these defines a leader of influence and integrity. In these pages we'll also meet some of Beebe's mentors: Steve Sample of USC, Harold A. "Red" Poling of Ford Motor Company, Richard Foster of Renovare, David McKenna of Asbury Seminary and Bob Emmons of Smart & Final. In a day of relentless self-direction, strong leaders have a critical role. With this book you can discover what it takes to be effective in your sphere of influence.
Principle 1 : the necessity of character : the foundation of effective leadership -- Principle 2 : the importance of competence : threshold competencies and the essentials of effective leadership -- Principle 3 : the advantage of team chemistry : the role of the CEO and the top management team in creating a climate of effectiveness and success -- Principle 4 : the interplay of culture and context : the dynamic relationship of organizational culture and environmental context -- Principle 5 : the strength of compatibility and coherence : discovering the right fit -- Principle 6 : leading with convictions : making life's greatest impact -- Principle 7 : maintaining our connections : facing our greatest leadership challenge -- Principle 8 : making an ultimate contribution : discovering life's greatest purpose -- Finis : when our time is up : making sure our life has mattered -- An overview of top management work in the twentieth century -- Robert Wuthnow's eight spheres of society.
Includes bibliographical references.
Keywords: Leadership; Leadership -- Moral and ethical aspects; Drucker, Peter F. -- 1909-2005.